2017
DOI: 10.1080/08830185.2017.1347649
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA mediated regulation of immunity against gram-negative bacteria

Abstract: Evidence over the last couple decades has comprehensively established that short, highly conserved, non-coding RNA species called microRNA (miRNA) exhibit the ability to regulate expression and function of host genes at the messenger RNA (mRNA) level. MicroRNAs play key regulatory roles in immune cell development, differentiation, and protective function. Intrinsic host immune response to invading pathogens rely on intricate orchestrated events in the development of innate and adaptive arms of immunity. We dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 179 publications
0
13
0
Order By: Relevance
“…MicroRNAs play important role in the regulation of immune response to different infectious agents ( 10 ). B. abortus is a facultative intracellular bacterium that can adapt to environmental stressor and replicates in phagocytic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs play important role in the regulation of immune response to different infectious agents ( 10 ). B. abortus is a facultative intracellular bacterium that can adapt to environmental stressor and replicates in phagocytic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we and others demonstrated that B. abortus could modulate the immune response through induction of regulatory cytokines such as IL-10 as negative regulation of pro-inflammatory cytokines, suggesting that this interplay between immune responses enables B. abortus persistence in the host ( 7 9 ). Recently, studies have increasingly reported the involvement of microRNAs (miRNAs) in the regulation of host responses to bacterial pathogens ( 10 ). miRNAs are small non-coding RNAs that negatively regulate gene expression by directly binding to the 3′ untranslated region (3′ UTR) of their mRNA targets.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs (microRNAs) are noncoding small RNA molecules capable of regulating gene expression at the post-transcriptional level [16]. Some host miRNAs have been reported to involve in the host-bacteria crosstalk [17,18], and miRNAs play important roles in modulating macrophages response toward pathogens, e.g. dynamic regulators of macrophage polarization and plasticity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…They can bind to the target mRNA, resulting in translational suppression or degradation of mRNA [13]. Due to the important function of microRNAs, they regulate approximately 30% of the gene transcription involved in a variety of cellular processes, including the immune response to invading pathogens [14]. The miRNAs (i.e., miR-223-3p, miR-150, miR-146b, miR-16, and miR-191), abundantly expressed in T cells, were down-regulated in human immunodeficiency virus (HIV) patients [15].…”
Section: Introductionmentioning
confidence: 99%